НОРМИРОВАНИЕ РАСХОДА ЭЛЕКТРОЭНЕРГИИ НА МЕТАЛЛУРГИЧЕСКИХ ПРЕДПРИЯТИЯХ С ИНДУКЦИОННЫМИ ПЛАВИЛЬНЫМИ ПЕЧАМИ - Муратов, Хаким; Хошимов, Фозилжон; Кадиров, Камолиддин (Innovatsion texnologiyalar, 2022)
The article gives a scientifically based method of rationing the consumption of electricity for the smelting of a ton of steel. This technique allows you to correctly analyze energy performance and assess the level of operation of existing equipment, to discover and realize unused reserves.